2021
DOI: 10.1002/advs.202103981
|View full text |Cite
|
Sign up to set email alerts
|

From Mesoscopic Functionalization of Silk Fibroin to Smart Fiber Devices for Textile Electronics and Photonics

Abstract: Bombyx mori silk fibers exhibit significant potential for applications in smart textiles, such as fiber sensors, fiber actuators, optical fibers, and energy harvester. Silk fibroin (SF) from B. mori silkworm fibers can be reconstructed/functionalized at the mesoscopic scale during refolding from the solution state into fibers. This facilitates the mesoscopic functionalization by engaging functional seeds in the refolding of unfolded SF molecules. In particular, SF solutions can be self-assembled into regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 141 publications
(372 reference statements)
0
45
0
Order By: Relevance
“…After a comprehensive literature survey comparing the temperature sensitivity of other works , (Figure d), the SCGC-2% CNFene film possesses a more sensitive temperature response (−5.2%/°C) and better mechanical properties, which is more conducive to the real-time monitoring of temperature in different scenarios.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…After a comprehensive literature survey comparing the temperature sensitivity of other works , (Figure d), the SCGC-2% CNFene film possesses a more sensitive temperature response (−5.2%/°C) and better mechanical properties, which is more conducive to the real-time monitoring of temperature in different scenarios.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, the larger the bending angle, the greater the deformation of the corresponding hydrogen bond network, so the electrical signal under the large bending angle is more evident than that under the slight bending angle. 42 Then, we compared the sensing performance of the films with and without CNFene and found that the sensing film 2) dual-mode E-skin (silk-nanofiber-derived carbon fiber membranes @ polymer film), 45 (3) Gr/SF/Ca 2+ films (multifunctional E-tattoo based on a graphene/silk fibroin/Ca 2+ (Gr/SF/Ca 2+ )), 20 (4) conducive ink (photolithographically printed flexible silk/PEDOT: PSS temperature sensors), 46 (5) 0.8 wt % MCNC/PVA (0.8 wt % multibranched nanocelluloses/polyvinyl alcohol (MCNC/PVA) composite films), 44 (6) fibrous sensor (silk composite electronic textile sensor), 47 (7) ionoelastomer (ionoelastomers are prepared through terminal functionalized block polymers F127DA and ethylammonium nitrate (EAN)), 43 (8) AgNW/CNF hybrid nanopaper (Ag nanowire/nanocellulose hybrid nanopaper), 48 (9) TS-gated device (TS-gated devices prepared from PUD/PEDOT:PSS/AgNWs), 49 and (10) smart composite (multilayer graphene/polystyrene composites). with CNFene added was more sensitive (Figures 5j and S6); the possible reason is CNFene improves the conductive network of the membrane and increases the hydrogen bond network, so when the material is deformed, the distance between the conductive units and the change of the hydrogen bond network affect the change of the electrical signal at the same time, 35 resulting in a more obvious change of the electrical signal of the sensing film with added 2% CNFene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks at 1645 and 1546 cm –1 in the inset represent the bending vibrations of the N–H bonds in the amide I and amide II regions of the protein, respectively. The results after deconvolution are displayed in Figure k, in which the contributions located at 1610–1642, 1642–1650, 1650–1660, 1660–1680, and 1680–1700 cm –1 can be assigned to the β-sheet, random coil, α-helix, β-turn, and β-antiparallel sheet, respectively. The relative ratios of these structural components are summarized in Figure l. About half of the SF consists of the β-sheet structure.…”
Section: Resultsmentioning
confidence: 99%
“…With increased temperature, I off of the device increased and V th shifted negatively, because the insulation resistance of silk protein decreased with elevated temperature. [52] The current values of device with different V read of −0.1, 0.1, and 0.3 V as a function of temperature are presented in Figure S8b (Supporting Information). Figure S8c (Supporting Information) depicts the current values from five devices, showing good device-todevice uniformity and similar temperature-dependent behaviors.…”
Section: Volatile Threshold Switching Mechanism Of Silk-based Devicesmentioning
confidence: 99%